(untitled) (Fiep Bulletin - online, 2014)
Introduction: The scientific literature shows the development impact of physical fitness on health. Objective: To assess the level of physical fitness in relation to sex in school is a public institution of elementary education - early grades. Methodology: A descriptive cross-sectional quantitative study. 31 students were studied, 19 males and 12 females, aged between 7 and 11 years, physical fitness tests proposed by PROESP being applied: 1 - Testing power of lower limbs; 2 - Test flexibility; 3 - Test speeds (20m race). Data were analyzed using descriptive statistics of mean and dispersion and is attested by the significance test (p<0,05) t -test for independent samples with post hoc Tukey test. Results: Data analysis showed no significant differences (p< 0,05) between sexes for variables regarding the power of the lower limbs (standing long jump) and speed test (20m). However, flexibility (sit and reach test) showed a statistically significant, positive difference to the boys. Conclusion: Boys performed better than girls in all three variables, being only significant difference in flexibility. Seems to be necessary to make programs that include mainly intended for girls in physical activity environments, and within schools this content is constant approach, seeking to assist in awareness of the need to move, as well as contributing to improved quality frameworks health.